Local knowledge, dynamism and the politics of struggle: A case study of the Hmong in Northern Thailand - Aranya Siriphon (2018)
The Hmong are not passive actors who wait for help from development workers and other authorities. Instead, they actively engage themselves within a process of social negotiation between unequal socio-economic and political groups, a 'dynamic knowledge system'. Three case studies from a Hmong Thantam community are used to better understand the process of social negotiation with multiple actors within complex power relations. More importantly, their dynamic local knowledge is used as a strategy to struggle against, and reconcile with, more powerful forces; the result of this process is the 'complexity' which happens as a response to power. It's possible to find knowledge from any place in the world when we humans learn from one another. Throughout the generations we Hmong have learned from many diverse sources. In order to fulfil our lives, we young Hmong still learn from the whole world. Laoyeng Saehang, A headman of Thantam village, Northern Thailand, 1998. © 2006 The National University of Singapore.